2014
DOI: 10.1074/jbc.m114.577429
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 (IL-17)-induced MicroRNA 873 (miR-873) Contributes to the Pathogenesis of Experimental Autoimmune Encephalomyelitis by Targeting A20 Ubiquitin-editing Enzyme

Abstract: Background:The regulatory mechanism of abnormal miRNA expression in astrocytes upon IL-17 stimulation remains unclear. Results: miR-873 induced by IL-17 promotes inflammatory cytokine production and aggravates demyelination in experimental autoimmune encephalomyelitis (EAE) through the A20/NF-B pathway. Conclusion: IL-17 regulates miRNA expression in astrocytes, which affects the pathogenesis of EAE. Significance: These data provide a novel regulatory mechanism in inflammatory autoimmunity diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 46 publications
9
78
0
Order By: Relevance
“…Many studies have demonstrated that the blockade of proinflammatory cytokines production in astrocytes can attenuate the damage of MS/EAE [19-21]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that the blockade of proinflammatory cytokines production in astrocytes can attenuate the damage of MS/EAE [19-21]. …”
Section: Discussionmentioning
confidence: 99%
“…Primary astrocytes from 0- to 1-day-old C57BL/6 mice were established as previously described [19]. Briefly, the cerebral cortices freed of meninges were dissected, minced and digested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reference literature [14, 21, 22], 0-2-days-old C57BL/6 mice were used. After sacrifice, the mice were soaked in 75% ethanol for 3-5 min, and the heads were cut off under sterile conditions with ophthalmic scissors.…”
Section: Methodsmentioning
confidence: 99%
“…IL-17 is a family of proinflammatory cytokines that consists of six ligands (IL-17A, B, C, D, E and F) that are produced by a subset of Th17 cells and that bind to their associated heteromeric transmembrane receptors (IL-17RA, B, C, D and E). Because they lack IL-17 and the IL-17 receptor, mice are less susceptible to the experimental induction of autoimmune encephalomyelitis (EAE) induction [12-14]. IL-17-specific inhibition attenuates inflammation, which suggests that IL-17 signaling plays an important role in the effector stage of EAE [15].…”
Section: Introductionmentioning
confidence: 99%